Social Outlook for Asia and the Pacific 2022 - United Nations (United Nations, 2022)
The Social Outlook is a flagship ESCAP publication produced every two years with a dedicated focus on social development issues in Asia and the Pacific. In 2022, under the theme of “The Workforce We Need”, the Social Outlook focuses on building a healthy, protected and productive workforce in Asia and the Pacific to achieve inclusive and sustainable development and build back better after COVID-19 pandemic, particularly in the presence of four key megatrends including climate change, ageing, digitalization and rising inequalities which has already prompted green, demographic and digital transitions that are altering the future world of work. Through its analysis, the Social Outlook aims to strengthen the evidence base and build capacity of policymakers on how to design and expand social protection, active labour market policies and health systems to achieve a resilient workforce today and in the future. The Report is structured along six chapters. Chapter 1 sets the latest social development context in the region highlighting the need for deepening solidarity and rebuilding trust to implement the 2030 Agenda on Sustainable Development. Next, Chapters 2-4 delve into three components of a resilient workforce, namely a healthy, productive, and protected workforce and emphasize the role of such a workforce in inclusive and sustainable development. Chapter 5 discusses policy recommendations for attaining such a workforce in Asia and the Pacific and proposes the renewal of the social contract which can put the region on a path for breakthrough and prosperity. Chapter 6 concludes.